Dengue reemergence in Argentina - Avilés, Gabriela (1999)
Aedes aegypti, eradicated from Argentina in 1963, has now reinfested the country as far south as Buenos Aires. In 1997, four persons with travel histories to Brazil, Ecuador, or Venezuela had confirmed dengue, and surveillance for indigenous transmission allowed the detection of 19 dengue cases in Salta Province. These cases of dengue are the first in Argentina since 1916 and represent a new southern extension of dengue virus.